Assessing banana stalk susceptibility to pathogens and their virulence - T. Desmarez; P. Brat; L. Lassois; B. Barral; O. Hubert (MethodsX)
The purpose of this protocol is to assess (a) the virulence of fungi on banana stalks and (b) the susceptibility of a banana stalk cutting modality/cultivar to a pathogen. The principle, plant material used, duration and expected results are presented. The materials and the five procedural steps—stalk sampling, inoculum and plant material preparation, pathogen inoculation, incubation, and evaluation of stalk necrosis—are detailed. Inoculum virulence and banana stalk susceptibility to pathogenic fungi are determined by measuring the proportion of necrosis.